Design Optimization and Performance Enhancement of Small-Scale Vortex-Induced Turbines for Sustainable Energy Generation - Sheikh Hassan, Sheikh Alif Habibullah; Mohd, Sofian (Research Progress in Mechanical and Manufacturing Engineering, 2024)
This study explores the development and evaluation of a vortex bladeless wind turbine prototype designed to harness wind energy in low wind speed conditions, making it suitable for regions like Malaysia. The prototype features a 2-meter tall, 0.2-meter diameter cylindrical structure on a flexible shaft that uses vortex-induced vibrations to generate mechanical energy. Testing in a wind tunnel with airflow from 1 m/s to 10 m/s, along with field tests around UTHM, demonstrates the turbine’s effectiveness at low to moderate wind speeds. The generated vibrations are converted into electrical energy using an electromagnetic induction system. Analysis of the test results, including oscillation frequency, voltage, and efficiency, shows promising performance where traditional turbines underperform. Enhancements based on these findings have further optimized the turbine’s performance.